Derivatization in Analytical Chemistry - Tzanavaras, Paraskevas D. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Derivatization is one of the most widely used sample pretreatment techniques in Analytical Chemistry and Chemical Analysis. Reagent-based or reagent-less schemes offer improved detectability of target compounds, modification of the chromatographic properties and/or the stabilization of sensitive compounds until analysis. Either coupled with separation techniques or as a "stand alone" analytical procedure, derivatization offers endless possibilities in all aspects of analytical applications.